Sonographic Criteria for Diagnosing Sentinel Node Metastases in Melanoma Patients - Ulrich, J.; van Akkooi, A. C.J.; Eggermont, A. M.M.; Voit, C. A. (Ultraschall in der Medizin - European Journal of Ultrasound, 2015)
Purpose: Ultrasound-guided fine needle aspiration cytology (US-FNAC) prior to surgical excision of a sentinel lymph node (SLN) is a new microinvasive approach for detecting micrometastases in melanoma patients. The aim of the current prospective study was to determine the sensitivity and specificity of the method and to define new diagnostic generally applicable ultrasound criteria.Materials and Methods: In 800 consecutive patients suffering from malignant melanoma of stage I/II, the SNs were examined sonographically after lymphoscintigraphy. US-FNAC was performed in all suspicious lesions in 302 patients. All patients underwent surgical removal of the SLN. The final histopathology and sonographic findings were correlated.Results: After a follow-up of 37 months and a given median tumor thickness of 1.6 mm in our cohort, 21 % of the patients had a positive SLN in the histologic examination. We calculated a sensitivity and specificity of US-FNAC of 56 % and 99 %, respectively. The positive and negative predictive values were 92 % and 89 %, respectively. The highest positive predictive values were achieved using the ultrasound criterion of peripheral perfusion in power mode. The sensitivity of US-FNAC increased in parallel with an increasing pT stage of the primary tumor and increasing size of the largest diameter of the involved SN nest.Conclusion: Our prospective study shows the impact of ultrasound-guided FNAC in the staging of the SN prior to a planned SLNB. It proved to be an additional, cost-effective diagnostic tool that enhances the discriminatory power for the indication to perform SLNB and spares both the patient and the surgeon a second surgical procedure. Among the tested ultrasound criteria, peripheral perfusion (PP) showed the highest sensitivity for detecting early SN.
Keywords: lymphatic; tumor; biopsy; melanoma; metastases